Dora the explorer. Dora's Easter adventure [videorecording (DVD)] - Gifford, Chris; Walsh, Valerie; Weiner, Eric (Paramount, 2012)
Get ready for an egg-citing Easter adventure as kids help Dora and Boots save the Hip-Hop-Bunny's basket of eggs! Plus, a troll wedding and a trip to Troll Land!